2011
DOI: 10.1021/ja206980q
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Tyrosine Nitration

Abstract: Tyrosine nitration, often observed during neurodegenerative disorders under nitrative stress, is usually considered to be induced chemically either by nitric oxide and oxygen forming nitrogen dioxide or by the decomposition of peroxynitrite. It can also be induced enzymatically by peroxidases or superoxide dismutases in the presence of both hydrogen peroxide and nitrite forming nitrogen dioxide and/or peroxynitrite. In this study, the role of cupric ions for catalyzing tyrosine nitration in the presence of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 66 publications
4
56
0
Order By: Relevance
“…The oxidant H 2 O 2 , which was used alone in the present study, can mainly oxidize Met residues to methionine sulfoxide [22]. The oxidation of His or Tyr residues by hydroxyl radicals and other ROS may also affect PrP misfolding and neurotoxicity [65][66][67][68].…”
Section: Discussionmentioning
confidence: 89%
“…The oxidant H 2 O 2 , which was used alone in the present study, can mainly oxidize Met residues to methionine sulfoxide [22]. The oxidation of His or Tyr residues by hydroxyl radicals and other ROS may also affect PrP misfolding and neurotoxicity [65][66][67][68].…”
Section: Discussionmentioning
confidence: 89%
“…In the presence of H 2 O 2 ,N i-ATCUN-ORP can produce hydroxyl radicals (see EPR experiments);t hus, nitration of tyrosine shouldb eo btained from this H 2 O 2 /NO 2 À system by Fentonr eaction pathway,l ike the Cu and Fe systems. [6,7] Nevertheless, our in vitro model system is unablet op roduce 3-NT with the H 2 O 2 /NO 2 À system. It is suggested that the methionine residue is very close to Ni II -ATCUN in ATCUN-ORP and it can be easily oxidizedb yt he hydroxyl radical to produce methionine sulfoxide, [27] which was detected by NMR spectroscopy (see Figure 3, NMR section).…”
Section: àmentioning
confidence: 89%
“…[5] In addi-tion, in the presence of H 2 O 2 ,m etal ions (Fe II and Cu II )g enerate hydroxyl radicals (HOC)t hat oxidizeN O 2 À to CNO 2 by Fenton reactions,l eadingt ot he production of 3-NT. [6,7] So far,m ost of the studies have been focusedo nF e-, Cu-, and Mn-based tyrosine nitration. However,N i II ions have not been considered for this reactionu ntil now.F ree Ni II ions are physiologicallyr edox inactive, and their toxicityi nv ivo has been relatedw ith activation by coordination with peptides and proteins with the histidine-containing motif (XXH) in the N-terminus, called ATCUN motif, which is found in several naturally occurring proteins.…”
mentioning
confidence: 99%
“…In LEPA, the electrochemical aspect of ionization methods of MS has been studied. [13] Under this topic, LEPA has used microfluidic chips to combine the electrochemical/chemical redox reactions with MS analysis, [14,15] investigated the photo-electrochemical principle of matrix-assisted laser desorption/ionization (MALDI), [16] and developed a number of ionization devices for MS. [17] Recently, there is a wide interest in the development of ambient ionization methods that produce ions from untreated samples under ambient conditions for high throughput analysis and to maintain the original state of the sample during analysis. [18] Electrostatic spray ionization (ESTASI) is an ambient ionization method, which has been developed by LEPA since 2012 and which is characterized by inducing the spray by electrostatic forces in order to reduce significantly the influence of the applied high voltage (HV) on the sample.…”
Section: Electrostatic Spray Ionization Mass Spectrometrymentioning
confidence: 99%